Norwegian Development Aid to Education. How Is Evaluation Used to Improve? - Welle-Strand, Anne (Acta Paedagogica Vilnensia, 2003)
For decades education has been a key focus of Norwegian public development aid. During recent years heavy criticisms have been raised about its efficiency and the administration’s professional competence has been questioned. It is suggested that lack of evaluation skills and knowledge cause many failures. Evaluation has both a learning aspect and is concerned with the extent program goals are achieved. An empirical study on Norwegian development aid to education is presented and discussed, and possible reasons for the criticism is analysed. A historical legacy of "practicism" being preferred to academic based competence, populist ideals, an affluent national economy and the fact that ’education’ in itself is a diffuse field – are among the reasons for the present unfortunate situation. In order to increase relevant competence, and by consequence, more goal effective aid, certain structural and training means are suggested.